EDUTOURISM TRAINING TO IMPROVE COMMUNITY EMPOWERMENT AT TOURISM VILLAGE - Maryani, Enok; Indrianty, Septy (Universitas Djuanda, 2022)
Ciburial tourist village is a village that has a beautiful landscape and an interesting cultural diversity. Various kinds of tourism potential are divided into several parts, namely cultural and artistic tourism, culinary tourism, and nature tourism. Judging from its natural and cultural conditions, Ciburial tourism village has the potential to be developed as an Edutourism. Based on these conditions, the purpose of the community service program is in the form of training on understanding Edutourism, the potential that can be explored as Edutourism, and steps for implementing Edutourism. The service method is carried out in several ways, namely observation to identify the potential of Edutourism, interviews with various sources, and training provided to the community regarding Edutourism. Based on the results it was found that the potential that could be developed into Edutoursim was culinary and cultural tourism, namely honey cultivation, tofu factories, and also bamboo crafts. After knowing the potential for edutourism in Ciburial, the concrete implementation steps that need to be taken next are planning, execution, continuous development, and cooperation. Cooperation with partners and also educational institutions need to be established to increase the level of visits to the Ciburial Tourism Village